The impact of an e-learning environment based on artificial intelligence in developing e-learning skills among female students of the College of Education at Umm Al-Qura University - Al-Mutairi, Alia Zaid (Journal of Curriculum and Teaching Methodology, 2022)
The current study aimed to measure the impact of an e-learning environment based on artificial intelligence in developing e-learning skills for female students of the College of Education at Umm Al-Qura University. , provided that the experimental group is trained using an electronic learning environment based on artificial intelligence, and that the students of the control group are trained using the lecture method, and for that the researcher designed a cognitive test to measure the cognitive aspects and a note card to measure the performance aspect, and the study showed that there are statistically significant differences between The average scores of the experimental group students in developing the cognitive and performance aspects of e-learning skills in both the pre- and post-applications, and this difference was in favor of the post-application. Artificial intelligence in the university’s female students’ curricula.
Keywords: Artificial Intelligence; E-Learning; Umm Al-Qura University